Swedish Spring Wheat Varieties with the Rare High Grain Protein Allele of NAM-B1 Differ in Leaf Senescence and Grain Mineral Content - Asplund, Linnea; Bergqvist, Göran; Leino, Matti; Westerbergh, Anna; Weih, Martin (PLoS ONE, 2013)
Some Swedish spring wheat varieties have recently been shown to carry a rare wildtype (wt) allele of the gene NAM-B1,known to affect leaf senescence and nutrient retranslocation to the grain. The wt allele is believed to increase grain proteinconcentration and has attracted interest from breeders since it could contribute to higher grain quality and more nitrogenefficientvarieties. This study investigated whether Swedish varieties with the wt allele differ from varieties with one of themore common, non-functional alleles in order to examine the effect of the gene in a wide genetic background, and possiblyexplain why the allele has been retained in Swedish varieties. Forty varieties of spring wheat differing in NAM-B1 allele typewere cultivated under controlled conditions. Senescence was monitored and grains were harvested and analyzed formineral nutrient concentration. Varieties with the wt allele reached anthesis earlier and completed senescence faster thanvarieties with the non-functional allele. The wt varieties also had more ears, lighter grains and higher yields of P and K.Contrary to previous information on effects of the wt allele, our wt varieties did not have increased grain N concentration orgrain N yield. In addition, temporal studies showed that straw length has decreased but grain N yield has remainedunaffected over a century of Swedish spring wheat breeding. The faster development of wt varieties supports thehypothesis of NAM-B1 being preserved in Fennoscandia, with its short growing season, because of accelerateddevelopment conferred by the NAM-B1 wt allele. Although the possible effects of other gene actions were impossible todistinguish, the genetic resource of Fennoscandian spring wheats with the wt NAM-B1 allele is interesting to investigatefurther for breeding purposes.